IOT Application in DUT High Frequency Measurement - Chong, Yi Chuan (Universiti Teknologi PETRONAS, 2017)
his report describes the development of an Internet of Things (IOT) application to remotely control network instrument, Rohde & Schwarz ZVL Network Analyzer (R&S ZVL). R&S ZVL is a manually operated instrument for network parameters analysis such as High Frequency Measurement. In this study, the application created allows the user to remotely control the instrument, R&S ZVL with a host PC. Standard Commands for Programmable Instruments (SCPI) and Virtual Instrument Software Architecture (VISA) are used for the setup of instruments. Application is developed using Windows Presentation Foundation (WPF) which is a graphical development subsystem in Microsoft Visual Studio. Application is designed with customized graphical user interface (GUI) and able to identify and connect with one or more instrument.